Edu-Kit “Our Coffee” Development on Problem Based Learning Model for Vocational Agribusiness and Agrotechnology Programs on Material Separation Mixture - Fadilah, Sofiana Nur; Marfu'ah, Siti; Wonorahardjo, Surjani (International Journal of Interactive Mobile Technologies (iJIM), 2020)
Student achievement in chemistry is relatively low because chemistry topics are not integrated with students’ expertise programs. The lack of variation in teaching material and learning model also reduces the motivation to study chemistry. One of the science-chemistry materials in vocational high schools is separation of mixture, taught in the agribusiness and agro technology specialization programs. Many business sectors such as cafes are starting to stand in the community, requiring coffee serving skills and also knowledge about coffee that can be viewed from the chemistry side. Chemical changes due to coffee cultivation and the processes through which coffee can be consumed can be learned through interactive and communicative teaching materials One way to present and integrate coffee topics in learning is to develop an Edu-Kit which contains problems in coffee that are integrated with separation of mixture topic. Separation of mixture is contained in the 2013 Curriculum. The choice of problem-based learning models is assessed according to the characteristics of vocational learning, which is to present real problems and solve them while learning the concepts needed. The Edu-Kit development uses the research and development (R&D) method of Borg and Gall. E-book was chosen as an application in the development of Edu-Kit which includes text, sound, picture and video. Validation data were collected from 2 validators and readability tests by students. Data were analyzed using quantitative and qualitative techniques. The effectiveness of the Edu-Kit uses quasi experimental, pretest and posttest designs. There were 62 samples determined by the saturation sampling technique. The sample is divided into two classes, namely the experimental and control classes. Edu-kit effectiveness from posttest scores, analyzed using the Mann Whitney U Test using SPSS. The results of Edu-kit development obtained an average percentage of validation of 91.90% with very decent criteria. While the results of the effectiveness test showed that the use of Edu-kit made students' understanding better in mixed separation material.